Squamous Cell Carcinoma Arising in an Epidermoid Cyst of Cavernous Sinus: A Rare Occurrence - Ashvini Kolhe; Tanvi Gaitonde; Ayushi Dubey; Asha Shenoy (Indian Journal of Neurosurgery)
Epidermoid cysts (ECs) account for 0.2 to 1.8% of all intracranial tumors and are even rarer in the cavernous sinus. They are benign with a favorable prognosis following surgical resection, but rarely can undergo malignant transformation to squamous cell carcinoma (SCC). We hereby report the first case of SCC arising in an EC of the cavernous sinus. A 40-year-old woman presented with recurrent cyst in the left cavernous sinus. Thirteen years ago, she underwent a surgery for EC at the same site. Histopathology of the recent resection showed features of a primary SCC arising from the EC, fulfilling the Garcia criteria for malignant transformation. SCCs usually involve the brain as a manifestation of metastases from a primary located elsewhere in the body or as a result of direct local spread from a head and neck primary. Primary intracranial SCCs are rare and usually arise from malignant transformation of benign epithelial cysts. It may present itself at the initial clinical presentation or may develop following a variable lag period (3 months to 33 years) after resection of a previous benign cyst and has a dismal prognosis. Clinically, rapid deterioration, recurrence, or failure to recover following surgery for a benign cyst along with contrast-enhanced computed tomography or magnetic resonance imaging findings on the lesion should raise suspicion for malignant transformation.